Penerapan Metode Dempster Shafer dalam Sistem Pakar Diagnosis Penyakit Diabetes Melitus - Setiawan, Muhammad; Putri, Raissa Amanda (Program Studi Teknik Informatika Universitas Pamulang, 2024)
Diabetes Mellitus (DM) is a lifelong chronic disease that significantly affects people's quality of life and incurs significant medical costs. Diabetes can lead to various complications of dangerous diseases and requires long-term treatment. Lack of public knowledge about the general and specific symptoms of Diabetes Mellitus causes delays in handling Diabetes Mellitus. This study aims to form an expert system application based on WEB that can diagnose Diabetes Mellitus from the symptoms experienced by patients in accordance with the provisions of an expert, through the application of the Dempster Shafer method. The results of this study show that the application of the Dempster Shafer method resulting from disease symptoms that have been inputted, namely in the form of disease symptoms that have been processed by the system and have been refined into a web-based application. From this application, it is expected to help the general public in the examination of Diabetes Mellitus.